Is there a rainbow after the rain? How do agricultural shocks affect non-farm enterprises? Evidence from Thailand - Katharina Grabrucker; Michael Grimm (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2018)
Increasing weather volatility poses a significant threat to the livelihood of rural households in developing countries. While how rainfall shocks affect agricultural households has been well documented, there is not much evidence on the indirect effects on non-agricultural households. Combining household panel data with grid-level precipitation data, we analyze how rainfall shocks affect non-farm enterprises in rural Thailand. We examine the effects of rainfall shocks on labor supply for independent, non-farm activities as well as the indirect effects of rainfall shocks on non-farm enterprises through forward linkages, backward linkages and the consumption levels of farm households. We find that farm households increase their labor participation in non-farm self-employment in response to rainfall shocks. We also observe that rainfall shocks lead to increased input costs by non-farm enterprises in the food processing industry, to higher input costs by farms, to higher sales by agriculture-related non-farm enterprises and to lower expenditure by farm households on food and other consumption items. These effects are significant for surplus rainfall shocks (i.e., more rainfall than usual) but less robust for deficit rainfall shocks (i.e., less rainfall than usual), yet both surplus and deficit rainfall shocks lower agricultural production compared to normal rainfall conditions.
Keywords: D22; J22; J46; Q12; R11; 330; Rainfall shocks; Non-farm enterprises; Farm/Non-farm linkages; Thailand